GENOTOXICITY OF N-HYDROXY AND AMINOPHENOL METABOLITES OF 2,6- AND 3,5-DIMETHYLANILINE AT THE HYPOXANTHINEGUANINE PHOSPHORIBOSYLTRANSFERASE LOCUS IN TK6 CELLS - Moon, Seo Hyun; Kim, Min Young (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study as to characterize the genotoxicity of reactive metabolites of 2,6-dimethylaniline (2,6-DMA) and 3,5-DMA in the hypoxanthineguanine phosphoribosyltransferase (HPRT) gene of human lymphoblastoid TK6 cells. Methods: Cultures were exposed to N-hydroxylamine and aminophenol metabolites of 2,6- and 3,5-DMA for 1 h in serum-free medium. Cell survival 24 h after exposure was determined by trypan blue exclusion. Cells were then subcultured for 7â€“10 days to allow to phenotypic expression of HPRT mutants. After the expression period, cells were plated in the presence of 2 Î¼g/ml 6-thioguanine for the selection of HPRT mutants. Plating efficiency was determined and mutant fraction calculated. Electron paramagnetic resonance (EPR) was also used to determine whether 3,5- dimethylaminophenol (DMAP) produced reactive oxygen species (ROS). Results: All of the metabolites tested were cytotoxic to these cells but exhibited a considerable variation in potency. The aminophenol metabolites of 2,6- and 3,5-DMA were considerably more toxic than the corresponding N-hydroxylamines. Furthermore, each metabolite of 3,5-DMA was more toxic than its 2,6-DMA counterpart; N-OH-3,5-DMA and 3,5-DMAP were clearly mutagenic at a level of 50 Î¼M. EPR studies showed intracellular oxidative stress induced under 3,5-DMAP treatment. Conclusions: Our findings suggest that genotoxic responses of 2,6- and 3,5-DMA are mediated through the generation of ROS by hydroxylamine and/ or aminophenol metabolites. Â 